Reward and Punishment Motifs in Chinese Fantasy Novel Liaozhaizhiyi - Treerattanawareesin, Pranchanok (Journal of Sinology (วารสารจีนวิทยา), 2017)
This research paper aims to study the reward and punishment motifs in 62 stories in the series of Chinese fantasy novel Liaozhaizhiyi by comparing to those in Stith Thompson’s Motif-index of Folk-literature. The results of this research reveal that the reward and punishment motifs in Liaozhaizhiyi and in Motif-index of folk-literature share some similarities and distinctions. The similar motifs convey human’s universal characteristics. Whereas the distinctive motifs illustrate the unique features of Chinese cultures which differ from other cultures. The reward and punishment motifs in Liaozhaizhiyi also portray the social concepts of Chinese people, including 1) the concept of multi-religious and beliefs in Chinese society, 2) the concept of ideal scholars, 3) the concept of social and political problems, and 4) the concept of ideal family. The study of the reward and punishment motifs in Liaozhaizhiyi reflects the images of Chinese society and their desires hidden in the miracles of fantasy novel.